Uma análise empírica da prova pericial no julgamento de ações que envolvem a saúde e segurança do trabalhador nas Varas do Trabalho de Curitiba - Balderrama, Luciana Vaz da Silva (2021)
The medical expertise in the Labor Court aims to guide the judge in his decisions in those actions involving accidents and diseases that are triggered within the scope of work. Some matters discussed in Labor Complaints, including actions involving work accidents need technical elements, where it permeates the need for an expert who should mostly be doctors, so that they can assist the judgment in their decisions. In this type of demand that is being processed in the Labor Court, the objective of the expert report is to establish the occurrence or not of an accident related to work, the establishment of the causal or concausal nexus and, finally, to verify the sequelae resulting from it that culminate in the inability or not of that worker for work life. Studies show that the medical expertise in Labor Justice brings great discussions about the reliability of this document, so important to assist the judgment in the preparation of their sentences and that it is a problem to be addressed since it is the life of the worker that is at stake and depending on the analysis made by the expert, may culminate in unfair decisions that do not perfectly meet the delivery of the judicial provision by the State. Most studies show that the expert is a liberal professional and who works in multiple roles within medicine and also, the low remuneration of his fees awarded by the judiciary can characterize a lack of interest and make this function so important, less attractive to these professionals. It is clear that judgments which are based solely on the report issued by the expert may lead to serious violations of procedural constitutional principles in the judicial provision, such as access to justice (Artigo 5, XXXV, CF/88), due process (Artigo 5, LIV, CF/88) and contradictory (Artigo 5, LV, CF/88), when the expert evidence produced in the work process is inadequate. Thus, within this context, the importance arises in know the importance of knowing the production of the expert evidence and its use as a starting point for the judge to form his conviction about the dismissal or not of the demand. This study seeks to analyze how the Labor Judges of the 9th Region judge the actions that involve cases of accidents and diseases related to work and how they appoint the medical experts of their trust to act in said demands that deal with actions that involve important requests for the worker's life, which concern their health and work capacity and fair compensation.